(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article presents the results of a study of patients with varicocele. In the study, the results of the examination and treatment of male patients of different ages after treatment with the drug detralex alone and in combination with other group of drugs are presented. The results of the study showed positive results for patients in all groups, both when using the drug detralex alone and when using it in combination. There were no side effects, exacerbation of diseases and development of complications in patients.